Education in contemporary Japan : - Okano, Kaori (Cambridge University Press, 2003)
This is the most informative book on Japanese education of the 1990s. The authors rely on a historical and qulitative approach to provide a welath of information about the functioning of contemporary Japanese education, with a special focus on the themes of inequality and diversity. This style of presentation should make the book attractive to a wide range of readers including undergraduates in anthropology, sociology, teacher education, and related courses...this is most comprehensive discussion of Japanese education to appear for some time. It is a good read and deserves the attention of a wide circle of readers." Journal of Japanese Studies